The Analysis Schematic Structure of Research Article from Journal Indexed by Sinta - Agung Yadira; T. Thyrhaya Zein; Eddy Setia (East Asian Journal of Multidisciplinary Research, 2022)
This study analyzes the schematic structure of Sinta's indexed research articles. The object of this research is in the form of fifteen indexed research articles of Sinta ranked 1 and 2. The schematic structure of this research article is then analyzed using SLF theory because this study is a study of the SFL genre. The researcher integrates the concept of Huang & Chen (2018). In conducting data analysis, this study adapted the interactive model of Miles, Huberman & Saldana (2014). It was found in this study that there are two structures in the research article, namely the mandatory structure and the optional structure. There are three mandatory structures, namely Reporting Findings (RF), Interpreting Findings (IF), and Literature Compare (LC), while Accounting Findings (AF) is not a mandatory phase. The rest are optional, namely; Explanation of Context (CE), Order of Presentation (SP), Restatement Analysis Procedure (RAP), Summarizing Findings (SF), Evaluation of Findings (EF), Recommending Further Research (RFS), Providing Pedagogical Implications (PI), Providing Pedagogical Implications (ISA). The analysis yielded (RAP)^(SF)^(CE)^(SP)^[[RF.IF]n.LC]^(AF)^(EF)^(RFS)^(PI)^(ISA).